THE INFLUENCE OF SERVICE QUALITY AND BRAND IMAGE ON CONSUMERS' DECISION TO CHOOSE PHENOM EVENT INDONESIA AS AN ORGANIZER OF MICE & EVENT ACTIVITIES - Kadek Aditya Nugraha; I Nengah Wirata; Indah Kusumarini (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2023)
This study aims to determine the effect of service quality (X1) and brand image (X2) on consumer decisions (Y) choosing Phenom Event Indonesia as the organizer of MICE & Event activities. The method used is a quantitative approach using the t test, F test and the coefficient of determination test (R2). The research data was collected by means of a documentation study and distributing questionnaires to 100 respondents. Based on the t test, it is known that the significant value of variable X1 is 0.616, variable X2 is 0.362. These two results show a positive value, so it can be said that the variable service quality (X1) and brand image (X2) have an effect on the consumer decision variable (Y).From the results of the F test it is shown that the calculated F value > F table, namely 156.806 > 3.09. This shows that service quality (X1) and brand image (X2) simultaneously have a positive and significant effect on consumer decisions (Y).Based on the Coefficient of Determination Test (R2) it is known that the variables of service quality (X1) and brand image (X2) simultaneously influence consumer decisions (Y) by 76.4%. This shows that service quality and brand image have a major influence on consumer decisions to use Phenom event Indonesia services.